PERLINDUNGAN HUKUM ANAK DALAM PERKAWINAN CAMPURAN DI SUMATERA BARAT - Wahyu Saputra; Anggun Lestari Suryamizon; Mahlil Adriaman (Ensiklopedia of Journal, 2023)
Citizenship or citizenship is one of the constitutive elements of the existence of a state, citizens are part of a population and become an element of the state and the constitution has an unbroken relationship with his homeland and with the country's constitution even though the person concerned is abroad. Citizenship indicates a legal relationship or mutual bond between the state and citizens. Citizenship is a very important basis for the state to determine who is a citizen and a foreigner. Based on the formulation of the problem mentioned above, the purpose of this study is to determine the rights and obligations of children in mixed marriages. To find out the legal protection for children from mixed marriages. This  method used in this study is descriptive, namely legal research on the enactment or implementation of normative legal provisions in action on every particular legal event that occurs in society. The result of this study is that children's rights become something that children deserve, and the children of mixed marriages live in Indonesia and the children of mixed marriages have not passed the age of 21 years / are not married, the children get the same legal protection as non-mixed children.Keywords: Child, Citizenship, Marriage